BEARING CAPACITY OF RAFT-PILE FOUNDATION USING TIMBER PILE ON SOFT SOIL - Tri Harianto; Muhammad Yunus; Muhammad Akbar Walenna (GEOMATE Journal, 2021)
Problematic soil (soft soil), generally require a soil improvement techniques. One of the concepts of soil reinforcement is to utilize timber as a material for raft-pile foundation. In this study, a circular containers were used as testing medium for the various model of reinforcement techniques (i.e. pile with different length embedded, raft and raft-pile foundation) including unreinforced model sample. The small-scale model tests were carried out in the laboratory and the numerical analysis conducted by using Plaxis3D. The raft and pile material using a locally available timber.The results show that the raft-pile foundation shows the smallest vertical deformation (settlement) compared to other types of foundations. The highest settlement reduction was observed in the raft-pile foundation which is almost 65% compared to unreinforced soil. Good agreement results were found between small-scale laboratory model test and numerical modelling, thus indicating the potential used of this foundation type by using local timber.